Nano-silver electrode material modified by anionic polymer and conductive polyaniline as well as preparation and application of nano-silver electrode material

By preparing Ag-FAA-PAN nano-silver electrode material, the efficiency and selectivity problems of carbon dioxide conversion to carbon monoxide are solved, and efficient and low-cost electrocatalytic conversion is achieved, which is suitable for industrial-grade current density and large-scale applications.

CN120330770APending Publication Date: 2025-07-18EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510562843.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The prior art is difficult to convert carbon dioxide into carbon monoxide efficiently and at low cost, and the conversion and selectivity of traditional nanosilver catalysts are limited, limiting large-scale industrial applications.

Method used

Commercial nanosilver powder and conductive polyaniline were used as binders to prepare Ag-FAA-PAN nanosilver electrode material by sonication and air spraying to form an Ag(III) cubic crystal structure, which was used for electrocatalytic reduction of CO2 to CO.

Benefits of technology

Among acidic electrolytes, CO selectivity is close to 90%, and the CO2 single conversion rate breaks through the limit of traditional nanosilver catalysts to 67.6%, and the CO2 loss is less than 1%. The synthesis process is simple and low-cost, which is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120330770A_ABST
    Figure CN120330770A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-silver electrode material modified by an anionic polymer and conductive polyaniline as well as preparation and application of the nano-silver electrode material. Commercial nano silver powder is used as a silver source, FAA and PAN are used as binders, the materials are mixed and subjected to ultrasonic treatment to prepare printing ink, the printing ink is sprayed on carbon paper, and the Ag-FAA-PAN nano silver electrode material with an Ag (III) cubic crystal structure is prepared. The catalyst is simple in preparation method and low in cost, has excellent selectivity for producing CO through electrocatalytic reduction of CO2 and industrial-grade current density, and is beneficial to large-scale industrial application: in a membrane electrode electrolytic tank containing an acidic electrolyte with the pH value of 1, the CO selectivity is close to 90% under the current density of 50 mA cm <-2 >; when the current is 400 mA and the CO2 inlet flow rate is 3 sccm, the CO2 single conversion rate of Ag-FAA-PAN breaks through the limitation that the conversion rate of a traditional nano-silver catalyst does not exceed 50% and reaches 67.6%, and the CO2 loss is less than 1%. In the field of preparing CO by electrocatalytic reduction of CO2, the catalyst has excellent catalytic performance and application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysts, and relates to a preparation method and application of a nano-silver electrode material modified by an anion polymer and conductive polyaniline. It also relates to its application in the preparation of oxygen evolution catalyst materials and oxygen evolution electrodes. This nano-silver electrode material has excellent performance as a catalyst in the electrocatalytic reduction of CO2 to produce CO, and also has potential application value in other energy development and environmental protection fields. Background Art

[0003] Developing clean and renewable energy and reducing the concentration of CO2 in the atmosphere have become one of the most urgent issues for humanity. Carbon capture, utilization, and storage (CCUS) are considered key technological solutions for global decarbonization. Compared with carbon capture and carbon storage, which are limited by high costs and technical difficulties, carbon utilization, as the key process of CCUS, can achieve high economic benefits by converting the captured CO2 into raw materials with high economic value.

[0004] Regarding the issue of CO2 utilization, many strategies have been developed. In recent years, various chemical methods for CO2 utilization and conversion have been preliminarily verified in laboratories and industrial production, such as biochemical, electrochemical, photochemical, radiochemical, and thermochemical methods. Among them, the electrochemical CO2 reduction reaction (CO2RR) has attracted wide interest in the scientific community because it can operate at room temperature and atmospheric pressure; the reduction products can be adjusted by changing external parameters, such as catalysts, electrolytes, and voltages; valuable fuels and chemicals, such as formic acid, methanol, ethanol, ethylene, and CO, can be generated, and further carbon-based fuels derived from petrochemical products can be produced, which will reduce the global demand for fossil fuels. Therefore, CO2RR is considered an ideal way to effectively reduce the concentration of CO2 in the atmosphere. Summary of the Invention

[0005] The present invention addresses the above problems and provides a nano-silver electrode material modified by an anion polymer and conductive polyaniline. Using commercial nano-silver powder as the silver source, and FAA ionomer and conductive polyaniline PAN as binders, after mixing, they are made into an ink by ultrasonic treatment and sprayed on carbon paper to form an Ag-FAA-PAN nano-silver electrode material with an Ag(III) cubic crystal structure. The preparation method of this catalyst is simple, with low cost, and has excellent selectivity for electrocatalytic reduction of CO2 to produce CO and industrial-grade current density. Moreover, the synthesis process does not require complex instruments, is easy to operate, and is conducive to large-scale industrial applications.

[0006] To achieve the above object, the specific technical solution adopted by the present invention is as follows:

[0007] In the first aspect of the present invention, a preparation method of the above-mentioned silver nanowire electrode material is provided, including the following steps:

[0008] (1) Thoroughly mix 5-20 parts by weight of commercial nano-Ag catalyst, 2.5-10 parts by weight of carbon black, 40-160 volumes of ionomer solution (Fumion FAA-3-EtOH-5), 2.5-10.0 parts by weight of conductive polyaniline, and 1-4 volumes of isopropanol, and ultrasonically treat for 30 min to form an ink solution;

[0009] (2) Spray the ink obtained in step (1) onto carbon paper using an airbrush, with a catalyst loading of 0.8-1.2 mg·cm -2 , and then place it in an oven at 100-120 °C to dry, obtaining the final Ag-FAA-PAN electrode material.

[0010] In the second aspect of the present invention, a silver nanowire electrode material modified with an anion polymer and conductive polyaniline is provided. The entire material is composed of spherical nano-Ag particles loaded on carbon paper and wrapped by FAA and PAN layers. The particle size is about 50-200 nanometers, the shape is irregular spherical, and a crystal structure mainly composed of Ag(III) crystal planes is formed; N belonging to the quaternary ammonium group at 402.1 eV and 399.2 eV and the characteristic peak of C-N and an obvious S signal peak belonging to the sulfonic acid group (-SO3H) in the range of 167-171 eV are observed by XPS; the characteristic peak of polyaniline is detected by infrared spectroscopy test at 500-1750 cm + ; -1 The characteristic peak of polyaniline is detected.

[0011] In the third aspect of the present invention, the application of the above-mentioned silver nanowire electrode material modified with an anion polymer and conductive polyaniline is provided. This material can be used as a low-cost and highly efficient electrocatalyst for the conversion reaction of carbon dioxide (CO2) to carbon monoxide (CO) under industrial-grade current. In a membrane electrode electrolytic cell containing a pH = 1 acidic electrolyte, at a current density of 50 mA·cm -2 , the CO selectivity is close to 90%; at a current of 400 mA and a CO2 inlet gas flow rate of 3 sccm, the single-pass conversion rate of CO2 of Ag-FAA-PAN breaks through the limit that the conversion rate of traditional silver nanowire catalysts does not exceed 50% and reaches 67.6%, and the CO2 loss is less than 1%. In the field of electrocatalytic reduction of CO2 to CO, it has excellent catalytic performance and application prospects.

[0012] Specifically, this material is used as a working electrode for electrocatalytically reducing CO2 to CO in an acidic electrolyte. The specific application method is as follows: A mixed solution of 1 mol / L Cs2SO4 and H2SO4 is used as the acidic electrolyte. A nano-silver electrode material modified with an anion polymer and conductive polyaniline is used as the working electrode, and an IrO2 / Ti electrode is used as the anode. The test is carried out in a membrane electrode assembly (MEA) electrolytic cell equipped with a proton exchange membrane. The test temperature is 10 - 40 °C, and the CO2 inlet gas flow rate is 3 - 50 sccm. In the acidic electrolyte, when the current density reaches 50 mA·cm -2 , the Faraday efficiency of CO reaches 90%. When the CO2 inlet gas flow rate is 3 sccm and the current is 400 mA, the single-pass conversion (SPC) exceeds 50%, and the SPC reaches 67.6%. This electrode can maintain a stable working state for more than 12 hours.

[0013] Therefore, preferably, a third aspect of the present invention provides the application of the above-mentioned nano-silver electrode material modified with an anion polymer and conductive polyaniline in the preparation of a CO2 electrolytic oxygen evolution electrode.

[0014] In a fourth aspect of the present invention, a CO2 electrolytic oxygen evolution electrode is provided, which includes a carrier and a catalyst material supported thereon. Among them, the catalyst material is the nano-silver electrode material modified with an anion polymer and conductive polyaniline prepared by the method described in any one of the above.

[0015] In a fifth aspect of the present invention, a method for electrocatalytically reducing CO2 to CO is provided, using the above-mentioned CO2 electrolytic oxygen evolution electrode as the working electrode. Preferably, the electrolyte is an acidic electrolyte formed by a mixed solution of 1 mol / L Cs2SO4 and H2SO4; the IrO2 / Ti electrode is used as the anode; the test temperature is 10 - 40 °C.

[0016] Compared with the prior art, the beneficial effects of the present invention are:

[0017] (1) The nano-silver electrode material of the present invention is prepared by simple ultrasonic treatment and air spraying. The catalyst preparation method is simple, the cost is low, and it has excellent selectivity for electrocatalytically reducing CO2 to produce CO and an industrial-grade current density. Complex instruments are not required during the synthesis process, the operation is convenient, which is conducive to large-scale industrial applications;

[0018] (2) Using an anion polymer and conductive polyaniline as Ag surface regulating molecules to synthesize Ag-FAA-PAN, the results show that it has excellent performance far exceeding the selectivity and single-pass conversion of traditional silver electrode materials for electrocatalytically reducing CO2. In a mixed solution of 1 mol / L Cs2SO4 and H2SO4, at 50 - 200 mA / cm 2In the current density range, the CO selectivity remains above 50%. Among them, at a current density of 50 mA cm -2 the CO selectivity is close to 90%; the single-pass conversion rate of CO2 breaks through the limit of no more than 50% for traditional silver nanocatalysts and reaches 67.6%, and the CO2 loss is less than 1%;

[0019] (3) During the preparation process, all reagents are commercial products and do not require further treatment;

[0020] (4) The synthesis method is simple, and the obtained materials are easy to apply, which is conducive to popularization and application in industrial production, and also has potential application value in other energy development and environmental protection fields. Description of the Drawings

[0021] Figure 1 Shows the X-ray diffraction patterns of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1 and the metal Ag standard card 04-0738;

[0022] Figure 2 Shows the X-ray photoelectron spectroscopy of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1;

[0023] Figure 3 Shows the infrared spectrum of polyaniline of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1;

[0024] Figure 4 Shows the scanning electron microscopy of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1;

[0025] Figure 5 Shows the transmission electron microscopy and the elemental energy spectra of C, N, S, and Ag of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1;

[0026] Figure 6 Shows the CO2 selectivity and the full cell potential diagram of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1 in an acidic electrolyte (1.0 M Cs2SO4 and H2SO4 mixed solution);

[0027] Figure 7 Shows the linear sweep voltammograms of the silver nanomaterial modified with anionic polymer and conductive polyaniline prepared in Example 1 in acidic (1.0 M Cs2SO4 and H2SO4 mixed solution) and neutral (0.1 M KHCO3) electrolytes;

[0028] Figure 8Shows the distribution of products and the single - pass conversion rate test at different CO₂ inlet rates at a current of 400 mA when the nano - silver material modified with anionic polymer and conductive polyaniline prepared in Example 1 is used in a membrane - electrode electrolytic cell with a mixed solution of 1.0 M Cs₂SO₄ and H₂SO₄ as the acidic electrolyte;

[0029] Figure 9 Shows the stability test of the nano - silver material modified with anionic polymer and conductive polyaniline prepared in Example 1 under the conditions of a current of 400 mA and a CO₂ inlet rate of 5 sccm. Detailed implementation manners

[0030] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the described embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.

[0031] The "ranges" disclosed herein are in the form of lower and upper limits. There can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, that is, any lower limit can be combined with any upper limit to form a range. For example, ranges of 100 - 140 and 500 - 900 are listed for a specific parameter, and ranges of 100 - 140 and 500 - 900 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1 - 2, 1 - 4, 1 - 5, 2 - 3, 2 - 4, and 2 - 5.

[0032] In the present invention, unless otherwise stated, the numerical range "a - b" represents an abbreviated representation of any real - number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 - 5" means that all real numbers between "0 - 5" are fully listed herein, and "0 - 5" is only an abbreviated representation of these numerical combinations.

[0033] In the present invention, if there is no special description, all the implementation manners and preferred implementation manners mentioned herein can be combined with each other to form new technical solutions.

[0034] Example 1

[0035] I. Preparation of Nano-Silver Electrode Material Modified with Anionic Polymer and Conductive Polyaniline

[0036] 10.0 g of commercial nano-Ag catalyst, 5.0 g of carbon black, 80 mL of ionomer solution (Fumion FAA-3-EtOH-5), 5.0 g of conductive polyaniline, and 2.0 mL of isopropanol were thoroughly mixed and ultrasonically treated for 30 min to form an ink solution; the obtained ink was sprayed on carbon paper using an airbrush, with a catalyst loading of 1.0 mg·cm -2 , and then placed in an oven at 100~120 °C for drying to obtain the final Ag-FAA-PAN electrode material.

[0037] II. Performance Characterization Tests

[0038] Figure 1 is the X-ray diffraction pattern of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1 and the metal Ag standard card 04-0738. It can be seen from it that the crystal structure of Ag-FAA-PAN is mainly based on the Ag(III) crystal plane;

[0039] Figure 2 is the X-ray photoelectron spectroscopy pattern of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1. It can be seen from it that the anionic polymer, polyaniline and nano-silver are successfully and tightly combined, and do not affect the structure and valence state of nano-silver itself;

[0040] Figure 3 is the infrared spectrum of polyaniline of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1, further proving that polyaniline is successfully modified on the surface of nano-silver;

[0041] Figure 4 is the scanning electron microscopy image of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1. It can be observed that the whole material consists of spherical clusters composed of nanoparticles, with the particle size being about 50~200 nanometers and the shape being irregular spherical; there is obviously a layer of coating on the surface of the nanoparticles, and the coating effect is good;

[0042] Figure 5 is the transmission electron microscopy image and the elemental energy spectrum diagrams of C, N, S, and Ag of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1. It can be seen from it that the C, N, and S elements are evenly distributed on the surface of Ag nanoparticles, confirming that the coating is indeed FAA and PAN.

[0043] III. Electrochemical Performance Tests

[0044] In the MEA membrane electrode electrolytic cell, using a CHI 660E electrochemical workstation, a standard two-electrode system was adopted. A mixed solution of 1.0 M Cs2SO4 and H2SO4 was used as the electrolyte. A gas diffusion electrode loaded with nanosilver and carbon black modified by anionic polymer and conductive polyaniline was used as the working electrode, and an IrO2 / Ti electrode was used as the anode. The cathode chamber and the anode chamber were separated by an ion exchange membrane, and the test temperature was room temperature. The gas flow rate on the cathode side was controlled at 20 sccm (10, 5, or 3 sccm), and a CHI1242C potentiostat was used to record electrochemical data. Gas chromatography (RAMIN, GC2060) was used to analyze the gas products of CO2 electroreduction, equipped with a flame ionization detector (FID, for detecting CO) and a thermal conductivity detector (TCD, for detecting H2), and Ar was used as the carrier. When the CO2 flow rate was 20 sccm, an on-line injection method was adopted. When the flow rates were 10 sccm, 5 sccm, and 3 sccm, a soap bubble flowmeter was used to recalibrate the outlet flow rate, and then the outlet gas was diluted for off-line detection.

[0045] Figure 6 Shows the CO2 selectivity and the full cell potential diagram of the nanosilver material modified by anionic polymer and conductive polyaniline prepared in Example 1 in an acidic electrolyte (a mixed solution of 1.0 M Cs2SO4 and H2SO4). It can be seen that after being modified by anionic polymer and conductive polyaniline, the CO selectivity of nanosilver has increased significantly. In the current density range of 50~200 mA·cm -2 the CO selectivity remains above 50%; at a current density of 50 mA·cm -2 the CO selectivity is close to 90%.

[0046] Figure 7 Shows the linear sweep voltammograms of the nanosilver material modified by anionic polymer and conductive polyaniline prepared in Example 1 in acidic (a mixed solution of 1.0 M Cs2SO4 and H2SO4) and neutral (0.1 M KHCO3) electrolytes. It can be seen that there are gradually differences in the current densities of the two electrolytes at different potentials as the inlet gas flow rate decreases.

[0047] Figure 8It shows the test of the distribution of products and single-pass conversion rate at different CO2 inlet rates at a current of 400 mA in a membrane electrode electrolytic cell using the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1 with a mixed solution of 1.0 M Cs2SO4 and H2SO4 as the acidic electrolyte. It can be seen that after applying the acidic electrolyte, the single-pass conversion rate of the material breaks through the limit that the conversion rate of traditional nano-silver catalysts does not exceed 50%, and a single-pass conversion rate of 67.6% is achieved at a flow rate of 3 sccm, reducing the proportion of CO2 loss to less than 1%.

[0048] Figure 9 It shows the stability test of the nano-silver material modified with anionic polymer and conductive polyaniline prepared in Example 1 under the conditions of a current of 400 mA and a CO2 inlet rate of 5 sccm. It can be seen that the material works continuously for 12 h under these conditions and has good stability.

[0049] Based on the above results, compared with the existing methods for preparing materials for electrocatalytic reduction of CO2 to produce CO, the present invention has the following advantages: the material synthesis operation is simple and large-scale preparation can be achieved; the raw materials are simple to manufacture and have low costs, and have excellent electrocatalytic selectivity and activity for producing CO, and can achieve efficient conversion of CO2 to CO under the conditions of low energy input and industrial-grade current.

[0050] Example 2

[0051] 5.0 g of commercial nano-Ag catalyst, 2.5 g of carbon black, 40 mL of ionomer solution (Fumion FAA-3-EtOH-5), 2.5 g of conductive polyaniline and 1.0 mL of isopropanol were fully mixed and ultrasonically treated for 30 min to form an ink solution; the obtained ink was sprayed on carbon paper using an airbrush, and the catalyst loading was: 1.0 mg cm -2 , and then placed in an oven at 100-120 °C to dry to obtain the final Ag-FAA-PAN electrode material. After testing, the characteristics and performance are similar to those of Example 1.

[0052] Example 3

[0053] 20.0 g of commercial nano-Ag catalyst, 10.0 g of carbon black, 160 mL of ionomer solution (Fumion FAA-3-EtOH-5), 10.0 g of conductive polyaniline and 4.0 mL of isopropanol were fully mixed and ultrasonically treated for 30 min to form an ink solution; the obtained ink was sprayed on carbon paper using an airbrush, and the catalyst loading was: 1.0 mg cm -2, and then placed in an oven at 100~120 °C for drying to obtain the final Ag-FAA-PAN electrode material. After testing, the characteristics and properties are similar to those of Example 1.

[0054] In summary, the materials obtained in the present invention can be applied to the electrocatalytic reduction of CO2 to produce CO. The application of the prepared nano-silver material modified with anionic polymer and conductive polyaniline for the electrocatalytic reduction of CO2 to produce CO is carried out at room temperature and normal pressure. During application, a mixed solution of 1.0 M Cs2SO4 and H2SO4 is used as the electrolyte; in the MEA membrane electrode electrolytic cell, a standard two-electrode system is adopted, and a gas diffusion electrode loaded with nano-silver and carbon black modified with anionic polymer and conductive polyaniline is used as the working electrode, and the IrO2 / Ti electrode is used as the anode.

[0055] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the described embodiments. Those skilled in the art can also make various equivalent variations or substitutions without departing from the spirit of the present invention, and these equivalent variations or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A preparation method of a nano-silver electrode material modified by an anionic polymer and conductive polyaniline, characterized in that, It includes the following steps: Using nano silver powder as the silver source, FAA ionomer and conductive polyaniline PAN as binders, after mixing, it is made into an ink by ultrasonic treatment and sprayed on carbon paper to prepare an Ag-FAA-PAN nano silver electrode material with an Ag(III) cubic crystal structure.

2. The preparation method according to claim 1, characterized in that, The preparation steps are as follows: (1) Sufficiently mix 5 - 20 parts by weight of nano silver catalyst, 2.5 - 10 parts by weight of carbon black, 40 - 160 volumes of FAA ionomer, 2.5 - 10.0 parts by weight of conductive polyaniline, and 1 - 4 volumes of isopropanol, and perform ultrasonic treatment to form an ink solution; (2) Spray the ink obtained in step (1) on carbon paper using an air spray gun, and then place it in an oven at 100 - 120 °C to dry to obtain the final Ag-FAA-PAN electrode material.

3. According to the preparation method described in claim 2, it is characterized in that: Among them, In step (1), the weight ratio between the nano silver catalyst and carbon black is 2:1, and the weight ratio with conductive polyaniline is also 2:1; The final concentration of the nano silver catalyst is 0.03 - 0.5 g / mL; The ultrasonic treatment time is 30 - 40 min.

4. According to the preparation method described in claim 2, it is characterized in that: Among them, In step (2), the loading amount of the nano-silver catalyst on the carbon paper is 0.8~1.2 mg·cm -2 .

5. A nano-silver electrode material modified by an anionic polymer and conductive polyaniline, characterized in that, It is prepared by using the method described in any one of claims 1 - 4.

6. The nano silver electrode material according to claim 5, wherein The material consists of nanoparticles forming spherical clusters, with the particle size being about 50 - 200 nanometers and the shape being irregular spherical.

7. Use of the nano silver electrode material modified with an anion polymer and conductive polyaniline described in claim 5 or 6 in the preparation of a carbon dioxide reduction electrocatalyst.

8. A carbon dioxide reduction electrode, characterized in that, It includes a carrier and a catalyst material supported thereon, wherein the catalyst material is a nano silver electrode material modified with an anion polymer and conductive polyaniline prepared by using the method described in any one of claims 1 - 4.

9. A carbon dioxide reduction method, characterized in that: Use the electrode described in claim 8 as the working electrode.

10. According to the method for electrolyzing water described in claim 9, it is characterized in that: Among them, Using a 1 mol / L mixed solution of Cs2SO4 and H2SO4 as the acidic electrolyte, a nano silver electrode material modified with an anion polymer and conductive polyaniline as the working electrode, an IrO2 / Ti electrode as the anode, and performing electrolysis in a MEA membrane electrode electrolyzer equipped with a proton exchange membrane, with the electrolysis temperature being 10 - 40 °C.